BUILDING THE TRANSLATION COMPETENCY OF FUTURE ENGLISH LANGUAGE TEACHERS - Sevinch Bakhtyorova (Western European Studies, 2024)
the article discusses the issue of formation of translation competence of future English language teachers and presents an individual approach
Keywords: future teacher; English language; translation competence